Analogy in grammar form and acquisition - Blevins, James P.; Blevins, Juliette (Oxford : Oxford University Press, 2009)
Leading researchers in morphology, syntax, language acquisition, psycholinguistics, and computational linguistics address central questions about the form and acquisition of analogy in grammar.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Analogy (Linguistics); Grammar, Comparative and general